The Contribution Of Puncak Lakude Tourism Object To Corn Farmers' Income In Masalili Village, Kontunaga Sub-District, Muna Regency - Isma, Isma; Abdul Gafaruddin; Samsul Alam Fyka (International journal of technology and education research, 2023)
This research aims to determine the income of corn farmers at the Puncak Lakude tourist attraction and to determine the contribution of farmers' income from the Puncak Lakude tourist attraction sector to corn farming income. Determining the research location was carried out purposively, this research was carried out from January to February 2022. The number of corn farmer respondents in the Puncak Lakude area was 15 people. The data analysis method used is descriptive qualitative analysis and income analysis. The results of this research show that the income of corn farmers after Puncak Lakude was IDR 932,433/Ha/MT with revenues of IDR 2,053,333/Ha/MT with total costs of IDR 1,360,900/Ha/MT.